# Solve for m fourth root of m+7+11=9 m+74+11=9
Move all terms not containing m+74 to the right side of the equation.
Subtract 11 from both sides of the equation.
m+74=9-11
Subtract 11 from 9.
m+74=-2
m+74=-2
To remove the radical on the left side of the equation, raise both sides of the equation to the power of 4.
m+744=(-2)4
Simplify each side of the equation.
Multiply the exponents in ((m+7)14)4.
Apply the power rule and multiply exponents, (am)n=amn.
(m+7)14⋅4=(-2)4
Cancel the common factor of 4.
Cancel the common factor.
(m+7)14⋅4=(-2)4
Rewrite the expression.
(m+7)1=(-2)4
(m+7)1=(-2)4
(m+7)1=(-2)4
Simplify.
m+7=(-2)4
Raise -2 to the power of 4.
m+7=16
m+7=16
Move all terms not containing m to the right side of the equation.
Subtract 7 from both sides of the equation.
m=16-7
Subtract 7 from 16.
m=9
m=9
Exclude the solutions that do not make m+74+11=9 true.
No solution
Solve for m fourth root of m+7+11=9

### Solving MATH problems

We can solve all math problems. Get help on the web or with our math app

Scroll to top